PENGARUH CAPITAL ASSET PRICING MODEL TERHADAP HARGA SAHAM (Studi pada Perusahaan – Perusahaan Sub Sektor Perbankan yang Listing di Bursa Efek Indonesia Periode 2014-2016) - Akram, Faisal Muhammad; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2017)
Stock Price influenced by demands and supplies of investor and issuer in stock exchanges. One of the investor aims in investing on company stocks are to get a high return. However, the higher return you get, the higher risk you take, so investor has to analyzing them to be balanced. To analyze that issue, Capital Asset Pricing Model is one of the solutions to analyze the stocks that deserves to be invested However, on the one hand CAPM has unrealistic assumptions in determining expected returns as well as risks and solve problems related to expected returns and risks. CAPM is not the only one model to describe it, so research is needed on the influence Capital Asset Pricing Model through stock prices.The aim of this Research is to understand the influence of the Capital Asset Pricing Model through the stock prices. The Population of this research is 27 companies that are listed on the banking sub sectored stocks in Indonesia Stock Exchange during the period of 2014 - 2016. Type of the research is explanatory research with quantitative approach. The analysis method used the coefficient correlation determination coefficient, simple regression, and significance test (uji t) on SPSS 16.0. Capital Asset Pricing Model is a model that has an expected return as the end result. There are several components in calculating the expected return, consist of actual return, market return, risk free return, and beta risk. Data analysis is done by testing the end result of Capital Asset Pricing Model in the form of expected return with stock price. The test results show Capital Asset Pricing Model has a positive and significant impact on stock prices. So if the component on the Capital Asset Pricing Model rises, the stock price will rise. As a suggestion, there will be better if a company undertake a safe investment strategy such as considering Capital Asset Pricing Model components to get high stock price.